Caribbean Literary Discourse : Voice and Cultural Identity in the Anglophone Caribbean - Lalla, Barbara (Book collections on Project MUSE., 2014)
Caribbean Literary Discourse is a study of the multicultural, multilingual, and Creolized languages that characterize Caribbean discourse, especially as reflected in the language choices that preoccupy creative writers. Caribbean Literary Discourse opens the challenging world of language choices and literary experiments characteristic of the multicultural and multilingual Caribbean. In these societies, the language of the master- English in Jamaica and Barbados-overlies the Creole languages of the majority. As literary critics and as creative writers, Barbar.